Anti-Infective, Anti-Inflammatory, and Immunomodulatory Properties of Breast Milk Factors for the Protection of Infants in the Pandemic From COVID-19 - Quitadamo, Pasqua Anna; Comegna, Laura; Cristalli, Pierpaolo (Frontiers in Public Health, 2021)
COVID-19 pandemic since the end of 2019 spreads worldwide, counting millions of victims. The viral invasion, systemic inflammation, and consequent organ failure are the gravest features of coronavirus disease 2019 (COVID-19), and they are associated with a high mortality rate. The aim of this study is to evaluate the role of breast milk in the COVID-19 pandemic, analyzing its antiviral, anti-inflammatory, and immunoregulatory effects due to its bioactive components, so numerous and important for the protection of infants. The study tried to demonstrate that all the components of human milk are capable of performing functions on all the pathogenic events recognized and described in COVID-19 disease. Those human milk factors are well-tolerated and practically free of side effects, so breast milk should become a research topic to discover therapies even in this epidemic. In the first part, the mechanisms of protection and defense of the breast milk elements will be delineated; in the second section, it will describe the human milk effects in viral infections and it will be hypothesized how the known mechanisms could act in COVID infection.